2012
DOI: 10.1002/jmri.23842
|View full text |Cite
|
Sign up to set email alerts
|

Role of standardized and study‐specific human brain diffusion tensor templates in inter‐subject spatial normalization

Abstract: Purpose To investigate the effect of standardized and study-specific human brain diffusion tensor templates on the accuracy of spatial normalization, without ignoring the important roles of data quality and registration algorithm effectiveness. Materials and Methods Two groups of diffusion tensor imaging (DTI) datasets, with and without visible artifacts, were normalized to two standardized diffusion tensor templates (IIT2, ICBM81) as well as study-specific templates, using three registration approaches. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…The results in this study show a slight improvement in reliability when using a study-specific template; however, in three methods and two regions, age modeling slightly improved with the standard template. This perhaps supports previous findings that a high quality standard template combined with low-artifact data can provide comparable results to a study-specific template [40], unless a disease group is being studied [41]. However, we also found that the standard template was much sharper than the study template, so the consequent differences in white matter masks may have also been a factor.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results in this study show a slight improvement in reliability when using a study-specific template; however, in three methods and two regions, age modeling slightly improved with the standard template. This perhaps supports previous findings that a high quality standard template combined with low-artifact data can provide comparable results to a study-specific template [40], unless a disease group is being studied [41]. However, we also found that the standard template was much sharper than the study template, so the consequent differences in white matter masks may have also been a factor.…”
Section: Discussionsupporting
confidence: 90%
“…The IIT DTI template version 4.1 [46] [47] was used for this purpose due to its high quality and use in related evaluation studies [40]. The imaging data was downloaded from the publicly available distribution on NITRC [48].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The multi-subjects spatial alignment was performed based on the voxel-wise maps of FA values (Jahanshad et al, 2013). Advanced, diffusion tensor-based spatial registration techniques have been advocated as an alternative approach to register DTI data (Wang et al, 2011)(Zhang and Arfanakis, 2013). Tensor-based alignment techniques such as those implemented in (http://dti-tk.sourceforge.net) use the similarity in voxel-wise diffusion tensors to drive multi-subject alignment.…”
Section: Discussionmentioning
confidence: 99%
“…A study‐specific template (SST) was built from 20 randomly selected subjects as it was previously shown that the use of a SST instead of already existing templates (e.g., N27 or MNI) improves the accuracy of the registration before the computation of the voxel‐wise atlases. The Advanced Normalization Tools (ANTs) was used for this task as it provides an adapted feature set for atlas creation.…”
Section: Methodsmentioning
confidence: 99%